Sustainable Strategy Development for Agro-Industrial SMIs Based on Process Performance Analysis: Integration of Value Stream Mapping, Eisenhower Matrix, and Interpretive Structural Modeling - Dzilalin Najmi; Andes Ismayana; Nastiti Siswi Indrasti (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop strategic recommendations for sustainable agro-industrial Small and Medium Industries (SMIs) in North Jakarta based on process performance analysis by integrating Value Stream Mapping (VSM), Eisenhower Matrix, and Interpretive Structural Modeling (ISM). A mixed-methods approach was employed, including field observations, in-depth interviews, literature review, and expert judgment to capture the actual conditions of agro-industrial SMIs comprehensively. Value Stream Mapping (VSM) analysis identifies the presence of non-value-added activities that contribute to production inefficiencies, indicating that the development of agro-industrial SMIs in North Jakarta remains at a basic level and highlighting the need to enhance the participation of SMI actors in development programs. The Eisenhower Matrix further classifies development factors into four strategic quadrants and generates seven alternative development strategies based on urgency and importance. Furthermore, ISM analysis reveals that strengthening the capacity of SMI facilitators is the key driving strategy that supports business feasibility and production standardization, digital and institutional ecosystem strengthening, and human resource development. These strategies subsequently enable technology integration and integrated environmental management of production, ultimately leading to the development of superior products based on innovation and market collaboration as the long-term strategic objective for sustainable SMI development in North Jakarta.